PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WAJIB PAJAK PENGGUNA E-SPT MASA PPN (STUDI PADA WAJIB PAJAK BADAN DI KANTOR PELAYANAN PAJAK MADYA MALANG) - Pratama, Febrian Karunia (Jurnal Mahasiswa Perpajakan, 2015)
Quality service to the public servant is one important thing. On the KPP Madya Malang quality of service is a major priority. The purpose of this research is to know and explain the influence of variable reliability, responsiveness, assurance, emphaty and tangible together and most dominant influence on the level of satisfaction of usersÂ of e-SPT theÂ VAT. The results indicates that all the independent variable of service quality has a simultaneously relation and a significant influence on customer satisfaction as the dependent variable. These results can be seen from F for 10.544 with probability (p) of 0.000 (p <0.05). While partially only variable reliability , and responsiveness that can demonstrate a significant effect of independent variables with the dependent variable. Variable responsiveness be the variable most dominant influence on customer satisfaction. Keywords: Service Quality, Satisfaction, e-SPT the VAT, taxpayer